Failure analysis on high temperature superheater Inconel 800 tube - Ahmad J.; Purbolaksono J.; Beng L.C. (2023)
This paper presents failure analysis on a super alloy Inconel 800 superheater tube in Kapar Power Station Malaysia. Visual inspection, microscopic examinations and creep analysis utilizing available related data are carried out to evaluate the failure mechanism and its root cause. The failed high temperature superheater (HTSH) tube was found snapped into two parts, heavily distorted shape and bent at several points. Microstructures of the failed tube showed that creep crack initiated at both external and internal surfaces of the tube and propagated as grain boundary creep cavities coalesced to form intergranular cracks. The severe geometry of tube causing steam flow starvation is identified to have caused increasing tube metal temperature resulting in overheating of the failed tube. Creep rupture is revealed as the cause of failure of the superheater tube. 2009 Elsevier Ltd. All rights reserved.